2020
DOI: 10.2174/1872211313666191030155837
|View full text |Cite
|
Sign up to set email alerts
|

Recent Patents on Permeation Enhancers for Drug Delivery Through Nails

Abstract: : The human nail is a unique barrier with a keratinized constitution that favors protection and fine touch. However, many disorders can affect the nail, among them, are the onychomycosis and psoriasis. Systemic oral therapy has been applied to treat these diseases, even presenting disadvantages, including side effects, drug interactions, contraindications, toxicity, high cost and low patient compliance. A great option to succeed in dealing with the problems associated with oral therapy is the topical administr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 69 publications
0
11
0
Order By: Relevance
“…Physical permeation enhancing methods includes etching, lasers, electropulsation, ultrasound, microneedling, hydration and iontophoresis, which either increase the surface area of application, introduce holes for deeper penetration or separate the keratin strands of the nail plate allowing larger molecules to penetrate. 163 An example of etching or microneedling is illustrated by a recent US patent that describes a nail treatment kit that etches 1 mm sized holes in the nail while dispensing antifungal treatment. 164 Iontophoresis, on the other hand, employs a small amount of electric current to enhance the delivery of the topical drug to the infected site.…”
Section: Novel Topical Therapiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Physical permeation enhancing methods includes etching, lasers, electropulsation, ultrasound, microneedling, hydration and iontophoresis, which either increase the surface area of application, introduce holes for deeper penetration or separate the keratin strands of the nail plate allowing larger molecules to penetrate. 163 An example of etching or microneedling is illustrated by a recent US patent that describes a nail treatment kit that etches 1 mm sized holes in the nail while dispensing antifungal treatment. 164 Iontophoresis, on the other hand, employs a small amount of electric current to enhance the delivery of the topical drug to the infected site.…”
Section: Novel Topical Therapiesmentioning
confidence: 99%
“…165 Chemical permeation enhancers include solvents, enzymes, etchants and keratolytic agents, which either hydrate the nail and/or break the bonds between the nail keratin strands, both resulting in larger pores or spaces for topical treatment to pass through. 163 Two recently patented topical formulations employ vastly different penetration enhancing and antifungal characteristics. The WO2019088055A1 patent describes a formulation containing a classic antifungal drug, such as efinaconazole or luliconazole, alongside the penetration enhancer ethyl lactate, among other volatile and non-volatile chemicals.…”
Section: Novel Topical Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…by authors in other topics. [12][13][14] In the present study, 174 homeopathy-related patents were found for the period analyzed. In an original way, the patents were analyzed by nationality and type of applicants.…”
Section: Wo2016011104 (A1) Gensco Lab Llc United Statesmentioning
confidence: 86%
“…Enhancement of antimycotic delivery using various solvents (dimethyl sulfoxide, methanol), enzymes, hydrogen peroxides, etc. were demonstrated for onychomycosis treatment as well [79, 80].…”
Section: Physical and Chemical Strategies To Enhancement Of Intra- Anmentioning
confidence: 99%